2015
DOI: 10.1177/1756283x15582139
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and precautions of endoscopic submucosal dissection for undifferentiated-type early gastric cancer

Abstract: Objectives: Since the development of techniques for endoscopic submucosal dissection (ESD), the indication range of endoscopic resection (ER) has been extended in early gastric cancer (EGC) treatment. For undifferentiated-type EGC, tumors with an intramucosal depth of invasion, no ulceration and a diameter of 20 mm or less were included in the expanded indications for ER in the Japanese Gastric Cancer Treatment Guidelines 2010. Nonetheless, because of difficulty in detecting lesions that meet the criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, the recurrence rate was much higher in the ESD group. Most previous studies reported that the overall survival rate of patients with UD-EGC treated with ESD was approximately 90% until the end of follow-up [ 14 , 32 - 34 ]. The interval of surveillance with esophagogastroduodenoscopy after ESD and after surgery was not identical in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recurrence rate was much higher in the ESD group. Most previous studies reported that the overall survival rate of patients with UD-EGC treated with ESD was approximately 90% until the end of follow-up [ 14 , 32 - 34 ]. The interval of surveillance with esophagogastroduodenoscopy after ESD and after surgery was not identical in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, comparisons between surgical specimens of mixed PDA and pure SRC have revealed higher frequencies of lymph node metastasis and submucosal invasion in the former [4][5][6]. Treatment outcomes and prognoses of UD-type EGCs after endoscopic treatment have also been studied, and the suitability of endoscopic treatment in these cases has been discussed [7][8][9]. However, mixed PDA and pure SRC have not been studied separately.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term outcomes, including en bloc resection, complete resection, curative resection, and complication rates of ER for UD-EGC, were reviewed (Table 2) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. En bloc resection was homogenously defined in the studies as the resection of the tumor in one piece with no endoscopically residual tumor, i.e., tumor resected in one piece without fragmentation.…”
Section: Short-term Outcomes Of Er For Ud-egcmentioning
confidence: 99%
“…Kang et al [22] who recorded a 0% local recurrence, reported that incomplete resection occurred when the tumor was resected in multiple fragments, with resected margins positive for cancer invasion or lymphovascular infiltration. The 5-year overall survival (5YOS) was reported to range from 93.0% to 98.6% in curative resection with the expanded criteria [17,19,26,28,29,31]. Inokuchi et al [28] reported a 5YOS of 93.3% after curative resection, with one patient mortality due to another disease at 49.3 months after ESD (data without cause of death).…”
Section: Long-term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation